Progressing Plastics Circularity: A Review of Mechano-Biocatalytic Approaches for Waste Plastic (Re)valorization - Nikolaivits, Efstratios; Pantelic, Brana; Azeem, Muhammad; Taxeidis, George; Babu, Ramesh; Topakas, Evangelos; Brennan Fournet, Margaret; Nikodinovic-Runic, Jasmina (Frontiers in Bioengineering and Biotechnology, 2021)
Inspirational concepts, and the transfer of analogues from natural biology to science and engineering, has produced many excellent technologies to date, spanning vaccines to modern architectural feats. This review highlights that answers to the pressing global petroleum-based plastic waste challenges, can be found within the mechanics and mechanisms natural ecosystems. Here, a suite of technological and engineering approaches, which can be implemented to operate in tandem with nature’s prescription for regenerative material circularity, is presented as a route to plastics sustainability. A number of mechanical/green chemical (pre)treatment methodologies, which simulate natural weathering and arthropodal dismantling activities are reviewed, including: mechanical milling, reactive extrusion, ultrasonic-, UV- and degradation using supercritical CO2. Akin to natural mechanical degradation, the purpose of the pretreatments is to render the plastic materials more amenable to microbial and biocatalytic activities, to yield effective depolymerization and (re)valorization. While biotechnological based degradation and depolymerization of both recalcitrant and bioplastics are at a relatively early stage of development, the potential for acceleration and expedition of valuable output monomers and oligomers yields is considerable. To date a limited number of independent mechano-green chemical approaches and a considerable and growing number of standalone enzymatic and microbial degradation studies have been reported. A convergent strategy, one which forges mechano-green chemical treatments together with the enzymatic and microbial actions, is largely lacking at this time. An overview of the reported microbial and enzymatic degradations of petroleum-based synthetic polymer plastics, specifically: low-density polyethylene (LDPE), high-density polyethylene (HDPE), polystyrene (PS), polyethylene terephthalate (PET), polyurethanes (PU) and polycaprolactone (PCL)) and selected prevalent bio-based or bio-polymers (polylactic acid (PLA), polyhydroxyalkanoates (PHAs) and polybutylene succinate (PBS)), is detailed. The harvesting of depolymerization products to produce new materials and higher-value products is also a key endeavor in effectively completing the circle for plastics. Our challenge is now to effectively combine and conjugate the requisite cross disciplinary approaches and progress the essential science and engineering technologies to categorically complete the life-cycle for plastics.